Effect of integrated nutrient management on sunnhemp (Crotalaria juncea) and its residual effect on succeeding rice (Oryza sativa) in eastern Uttar Pradesh - TRIPATHI, M K; MAJUMDAR, B; SARKAR, S K; CHOWDHURY, H; MAHAPATRA, B S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during summer and rainy seasons of 2003–05 at Sunnhemp Research Station, Pratapgarh, Uttar Pradesh to find out the effect of integrated nutrient management on yield, yield attributes and nutrient uptake by sunnhemp (Crotalariajuncea L.), its residual effect on succeeding rice (Oryza sativa L.) crop and residual fertility build-up in soil. The fibre yield of sunnhemp was significantly higher (0.76 tonnes/ha) with 75% NPK + Rhizobium + PSB (T5) over the control but was at par with 100% NPK & 75% NPK + Rhizobium, while significantly higher NPK uptake was observed with T5 over the other treatments. On the other hand, residual effect of integrated nutrient management on rice yield was nonsignificant but 75% NPK + Rhizobium + PSB recorded significantly higher nutrient uptake over the other treatments except100% NPK & 75% NPK + Rhizobium. The maximum net returns from sunnhemp (Rs 9 822/ha) was recorded with 75% NPK + Rhizobium + PSB with adequate soil fertility build-up under sunnhemp–rice cropping sequence in Inceptisol of eastern Uttar Pradesh.